Review of prophetic food: the Vitis species / Puteri Faten Fariheen Megad Mohd Nizar, Hannis Fadzillah Mohsin and Ibtisam Abdul Wahab - Megad Mohd Nizar, Puteri Faten Fariheen; Mohsin, Hannis Fadzillah; Abdul Wahab, Ibtisam (Center for Islamic Philantrophy & Social Finance (CIPSF), 2022)
Vitis species or the grapes, possess various natural constituents that can be found in their seeds, leaves and skin extracts. The active chemicals consist of polyphenols, flavonoids, stilbenes, alkaloids and volatile oils. Each of them contributes to pharmacological effects. This study is to highlight the Vitis species that are widely known for their health benefits. The historical uses of this plant include treating stomach pain, injury, and abdominal complaints. In addition, this herb was used as an ointment in treating eye and skin diseases. The medicinal properties of the grapes were reported as anticancer, antioxidant, anti-inflammatory, antimicrobial, cardioprotective, hepatoprotective and neuroprotective. The objectives of this study are to perform a literature search (from 2000 - 2020) and review the shortlisted publications on the Vitis species. From the online articles, the phytochemistry and pharmacological activity of the grapes were mentioned. The review included the traditional uses of the grapes. It is expected that the understanding of the chemical and biological activity of Vitis species may contribute to the development of new drugs.